2016
DOI: 10.1038/srep30235
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength grating enabled on-chip ultra-compact optical true time delay line

Abstract: An optical true time delay line (OTTDL) is a basic photonic building block that enables many microwave photonic and optical processing operations. The conventional design for an integrated OTTDL that is based on spatial diversity uses a length-variable waveguide array to create the optical time delays, which can introduce complexities in the integrated circuit design. Here we report the first ever demonstration of an integrated index-variable OTTDL that exploits spatial diversity in an equal length waveguide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we review recent progress on developing additional basic building blocks based on SWG waveguides in SOI for applications in optical communications and MWP, particularly optical filters and optical delay lines (ODLs). We describe how Bragg gratings (BGs) [20][21][22][23], microring resonators (MRRs) [20,21,24,25], contra-DCs [26][27][28], and optical add-drop multiplexers (OADMs) [29] can be implemented using SWG waveguide components, as well as how SWG waveguides enable index variable optical true time delay lines (OTTDLs) [30]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of these dispersions contribute significantly to limiting the bandwidth of the optical fiber [47].…”
Section: Introductionmentioning
confidence: 99%